Mathemathics for elementary teachers : - Bennett, Albert B. (McGraw-Hill, 2004)
Emphasizing conceptual understanding through the use of models and visuals, this text helps students connect ideas and concepts while providing them with useful methods for teaching math to elementary school children. Mathematics for Elementary Teachers: A Conceptual Approach addresses the NCTM standards by encouraging active student participation through features such as "Math Activities" and "Math Investigations." The "Math Investigations" now appear on the companion website.